Effect of Silicon Addition on Microstructure and Mechanical Properties of Chromium and Titanium Based Coatings - Ardila-Téllez, Luis Carlos; Sánchez-Moreno, José Manuel; Moreno-Téllez, Carlos Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The changes in the microstructure, mechanical properties and residual stresses of AlTiN, AlTiSiN, AlCrN and AlCrSiN coatings, has been studied before and after annealing at 900 ºC and 1100 ºC, using scanning and transmission electron microscopy, along with nano-indentation and X-ray diffraction techniques. The As-deposited coatings show a columnar structure, with a crystallite size between 18 nm and 28 nm. Despite the silicon addition, no effect on the crystallite size refinement was observed.However, the addition of silicon increases hardness, elastic modulus and compressive residual stresses. After annealing at 900 ºC, the crystallite size growth and the residual stress relaxes, therefore, the coating hardness decreases. At 1100 ºC, the oxide layers formed in AlTiN and AlTiSiN, which act as protective layers enhancing oxidation resistance, meanwhile, a complete oxidation of AlCrN and AlCrSiN coatings take place. The Titanium based coatings present some superior mechanical properties and oxidation resistance than the chromium based coatings at 900 ºC and 1100 ºC.